2013
DOI: 10.1590/s0103-05822013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos cuidados de proteção solar e prevenção do câncer de pele em pré-escolares

Abstract: Findings revealed that the use of sunscreen among preschoolers was incorrect and insufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
0
6
0
10
Order By: Relevance
“… 3 In the present study, SPF 30 was more frequently chosen by the students. Batista et al 7 described that 95.2% of preschoolers parents used SPF above 15. This seems to indicate that people know that a SPF 15 or lower sunscreen is less effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 In the present study, SPF 30 was more frequently chosen by the students. Batista et al 7 described that 95.2% of preschoolers parents used SPF above 15. This seems to indicate that people know that a SPF 15 or lower sunscreen is less effective.…”
Section: Discussionmentioning
confidence: 99%
“…Batista et al (2013) 7 applied questionnaires in 361 parents of preschool students in Santa Catarina in order to investigate their practices of skin care for their children and detected that sunscreens were used insufficiently and incorrectly. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Few studies have looked at sun protection in children with dark skin. In general, these studies have shown that parents and/or caregivers tend not to encourage children to adopt sun safe behaviours including the use of sun protection equipment because of a perception that their child’s dark skin provides adequate natural protection from UVR [ 11 , 12 ]. In Africa, no retrievable studies have considered mothers’ perceptions of the feasibility and acceptability of using sun protection equipment among small children with darkly pigmented skin.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, are young adults considered candidates to suffer damage from radiation, insofar as they are often exposed to sport and leisure activities. Subject to cumulative exposure over their lives, are more propense to influence conferred by the aesthetic appreciation of tanning and are in the most prone age group of unprotected exposure (7)(8)(9)(10) .…”
Section: Introductionmentioning
confidence: 99%